Characterization of Austrian severe asthma patients - Renner, Andreas; Stoshikj, Slagjana; Pohl, Wolfgang; Bal, Christina; Reisinger, Matthias; Löffler-Ragg, Judith; Zacharasiewicz, Angela; Buhl, Roland; Hamelmann, Eckard; Taube, Christian; Korn, Stephanie; Idzko, Marco (Respiratory medicine, 2023)
Introduction - The Severe Asthma Registry, founded by German Asthma Net (GAN) in 2011, is a prospective registry recording clinical parameters from participating centers in Germany, Austria and Switzerland. This article presents the baseline characteristics of severe asthma patients from Austrian centers. - Methods - We analyzed the baseline visit data of all patients recruited to the GAN Severe Asthma Registry from participating Austrian centers. - Results - Baseline visit data were available for 214 Austrian severe asthma patients from 6 Austrian centers from 2013 to 2022. Mean age was 53.7 years. Mean BMI was 26.4 kg/m2. More than a third (37.4%) of all patients had daily daytime asthma symptoms at baseline and had to use their reliever medication at least once per day. Forty-one percent of patients were classified as uncontrolled according to GINA and 24.8% as partially controlled at baseline visit. The median annual exacerbation frequency was 3 in the previous 12 months. At the time of baseline visit, 23.4% of all patients had regular treatment with oral corticosteroids. Furthermore, 23.9% had received any severe asthma monoclonal antibody prior to the baseline visit. There were no notable differences in baseline characteristics between patients categorized by smoking history or measurable type 2 inflammation. - Conclusions - This study provides the first multi-center characterization of Austrian severe asthma patients. Patients in this cohort had better asthma control and less frequent exacerbations compared to most international registries.